Metabolomics - what nomenclature to use? - Tamas Komives (Ecocycles, 2017)
This Opinion paper was written to initiate a discussion on the nomenclature used in metabolomic studies. The paper is based on the belief that the currently used classification of metabolites as "primary" and "secondary" are inaccurate and somewhat misleading. Of the alternative names previously suggested in the literature we strongly support the use of the names "general" and "specific metabolites" as replacements of "primary" and "secondary", respectively.